THE EFFECT OF LEVERAGE, COMPANY SIZE, AND SUSTAINABILITY REPORT DISCLOSURE ON COMPANY VALUE WITH BOARD OF COMMISSIONERS' COMPOSITION AS MODERATING VARIABLES (Study on Manufacturing Company Winner of Asia Sustainability Reporting Rating (ASRRAT) 2020) - Khamdani Ahmad; Kusumaningdiah Retno Setiorini (IJMA (Indonesian Journal of Management and Accounting), 2022)
This study aims to scientifically examine the effect of leverage, firm size, and sustainability report disclosure on firm value with the composition of the board of commissioners as a moderating variable in manufacturing companies that won the Asia Sustainability Reporting Rating (ASRRAT) 2020. This type of research is quantitative research with causal associative research design. The research population is a manufacturing company that won the Asia Sustainability Reporting Rating (ASRRAT) 2020 event for the 2016-2019 period. Obtained a sample of 13 companies using purposive sampling method. Data processing using IBM SPSS Statistic version 25 application with descriptive analysis, multiple linear regression, and MRA. The results of the study show that Leverage has a negative and significant effect on firm value, Firm Size has a positive and significant effect on firm value, Sustainability Report Disclosure has no effect on firm value. Leverage, Company Size and Sustainability Report Disclosure have a simultaneous effect on firm value. The composition of the board of commissioners which is reflected in the composition of the independent board of commissioners strengthens the influence of Leverage, Company Size and Sustainability Report Disclosure on Company Value. The determination value of Adjusted R Square is 0.213, which means that the value of the firm is influenced by the variables of Leverage, Company Size and Sustainability Report Disclosure of 21.3%, the remaining 78.7% is explained by other variables outside the research model